Autism spectrum disorder related phenotypes in a mouse model lacking the neuronal actin binding protein profilin 2 - Witke, Walter; Di Domenico, Marina; Maggi, Laura; Di Nardo, Alessia; Stein, Valentin; Pilo Boyl, Pietro (Frontiers in Cellular Neuroscience, 2025)
IntroductionProfilin 2 (PFN2) is an actin binding protein highly expressed in the brain that participates in actin dynamics. It has been shown in vitro and in vivo that in neurons it functions both post-synaptically to shape and maintain dendritic arborizations and spine density and plasticity, as well as pre-synaptically to regulate vesicle exocytosis. PFN2 was also found in protein complexes with proteins that have been implicated in or are causative of autism spectrum disorder.MethodsWe employ a genetically engineered knock-out mouse line for Pfn2 that we previously generated to study the mouse social, vocal and motor behavior in comparison to wild type control littermates. We also study neuronal physiology in the knock-out mouse model by means of cellular and field electrophysiological recordings in cerebellar Purkinje cells and in the Schaffer collaterals. Lastly, we study anatomical features of the cerebellum using immunofluorescence stainings.ResultsWe show that PFN2 deficiency reproduces a number of autistic-like phenotypes in the mouse, such as social behavior impairment, stereotypic behavior, altered vocal communication, and deficits in motor performance and coordination. Our studies correlate the behavioral phenotypes with increased excitation/inhibition ratio in the brain, due to brain-wide hyperactivity of glutamatergic neurons and increased glutamate release not compensated by enhanced GABAergic neurotransmission. Consequently, lack of PFN2 caused seizures behavior and age-dependent loss of cerebellar Purkinje cells, comorbidities observed in a subset of autistic patients, which can be attributed to the effect of excessive glutamatergic neurotransmission.DiscussionOur data directly link altered pre-synaptic actin dynamics to autism spectrum disorder in the mouse model and support the hypothesis that synaptic dysfunctions that asymmetrically increase the excitatory drive in neuronal circuits can lead to autistic-like phenotypes. Our findings inspire to consider novel potential pathways for therapeutic approaches in ASD.